IMPLEMENTATION OF “Freedom to Learn – Independent Campus (MBKM)” PROGRAM AT MUARA GEMBONG - Sukreni, Tulus; Untari, Dhian Tyas; Soehardi, Soehardi; Perdana, Timorora Sandha; Hutahaean, Erik Saut H; Khasanah, Fata Nidaul (Journal of Economic Development, Environment and People, 2022)
The aims of this study is to analysis the grand strategy to creat Muara Gembong as The Implementation o f"Merdeka Learning – Independent Campus (MBKM)”. The sources of the study are secondary data originating from books and publications related to "Merdeka Learning – Independent Campus (MBKM)” programs. In writing this paper, the author uses a qualitative research method using a library approach. Qualitative research is a particular tradition in social science that is fundamentally dependent on observing humans in their own area and relating to these people in their language and in their terminology. While the library approach is a study that uses data analysis based on written materials. Library materials in the form of published notes, books, magazines, newspapers, manuscripts, journals or articles. Hope that the results of the study become a influence for next research related to the development of "Merdeka Learning – Independent Campus (MBKM)” programs.